2015
DOI: 10.1016/j.foodchem.2015.01.079
|View full text |Cite
|
Sign up to set email alerts
|

Functional, thermal and rheological properties of oat β-glucan modified by acetylation

Abstract: Fibers of β-glucan have been added to foods for their thickening properties, their ability to form gel at low concentrations, but mainly for their appeal in health promotion. Current analysis evaluates the influence of acetylation (4% and 6% acetic anhydride for 10 and 20 min) on the functional, thermal, morphological and rheological properties of the concentrate containing 31% of oat β-glucan. The degree of substitution of the acetylated β-glucans ranged from 0.03 to 0.12, suitable for use in foods. Acetylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 30 publications
3
28
2
1
Order By: Relevance
“…The lower LGC of β‐glucans indicated their good gelation abilities. Earlier studies showed that 3% (Souza et al, ) and 12% (Moura et al, ) of oat β‐glucan concentrations were necessary to form a strong gel. LGC showed a negative correlation with magnesium ( r = −0.505; nonsignificant at p < 0.05) and copper ( r = −0.762, p < 0.05) and a positive correlation with ash content ( r = 0.560; nonsignificant at p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower LGC of β‐glucans indicated their good gelation abilities. Earlier studies showed that 3% (Souza et al, ) and 12% (Moura et al, ) of oat β‐glucan concentrations were necessary to form a strong gel. LGC showed a negative correlation with magnesium ( r = −0.505; nonsignificant at p < 0.05) and copper ( r = −0.762, p < 0.05) and a positive correlation with ash content ( r = 0.560; nonsignificant at p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The lower LGC of β-glucans indicated their good gelation abilities. Earlier studies showed that 3% (Souza et al, 2015) and 12% to processing (Vizhi & Many, 2014). β-glucan from OS-6 cv.…”
Section: Functional Propertiesmentioning
confidence: 98%
“…2. The strong absorption band at 3353 cm −1 (LAS-N) and 3380 cm −1 (LAS-C) is attributed to stretching vibration of O-H (Xu et al, 2009;Hu et al, 2011;Souza et al, 2015). The peak in the region 2930 cm −1 (LAS-N) and 2915 cm −1…”
Section: Discussionmentioning
confidence: 96%
“…The microstructure of β‐glucan gums was examined by a scanning electron microscope (JEOL, JSM‐5200, Tokyo, Japan) according to de Souza et al. (2015). The samples were sputter‐coated (SPI‐ Module TM Sputter Coater, SPI Supplies®, West Chester, PA, USA) with gold at vacuum evaporator at 25 kV accelerating voltage with different magnification power from 35 to 2,000×.…”
Section: Methodsmentioning
confidence: 99%
“…This interruption in the polymer permits water to get in between the chains and makes β‐glucan soluble in water. Therefore, consumptions of barley β‐glucan promote water absorption and form high‐viscous solutions in the gastrointestinal tract (de Souza et al., 2015; Vasanthan & Temelli, 2008), which offer many health benefits (approved by the U.S. Food and Drug Administration; FDA, 2018). In addition, β‐glucan molecular structure and concentration play an important role in its functional properties, especially water solubility, viscosity, and digestibility (Burkus & Temelli, 2000; Ryu, Lee, You, Shim, & Yoo, 2012).…”
Section: Introductionmentioning
confidence: 99%